Reinterpretation of Sexual Violence Theology: Case Study of Amina Wadud’s Tafsir - Sa'dan, Masthuriyah (Jurnal Perempuan, 2016)
Sexual violence in the history of humankind is a common phenomena. Ironically the object of violence is frequently women. Unfortunately, those violence are legitimated with doctrine. Cases of husband beating wife as nusyuz and other violences are legitimated with holytexts. Muhamad’s personality to his wives even being used as legitimation of theology. This made interpretation becomes bias. Amina Wadud’s tafsir indicated that there is a need to re-evaluate and reinterprete those bias tafsir.